Absolute radiometric and photometric measurements of near‐eye displays. Issue 4 (21st April 2017) - Penczek, John; Boynton, Paul A.; Meyer, Frederick M.; Heft, Eric L.; Austin, Richard L.; Lianza, Thomas A.; Leibfried, Lukas V.; Gacy, Luca W.
Abstract: The arrival of near‐eye displays has challenged the traditional methods that have been used to measure the optical properties of displays. Near‐eye displays typically create virtual images and are designed for the relatively small entrance pupil of the human eye. These two attributes result in optical measurement requirements that are substantially different from traditional flat panel displays. This paper discusses the optical system requirements needed to make absolute radiometric and photometric measurements of near‐eye displays. These guidelines are contrasted with the performance of current optical measurement instruments. An initial study was conducted using traditional and modified instruments and exhibited a significant variance in the results with different near‐eye display designs. The study demonstrated that some traditional optical instruments can yield erroneous results when used to measure near‐eye displays. Generic optical system design concepts were used to interpret the experimental results and helped to identify how current commercial designs could be modified to properly measure near‐eye displays. Abstract : Near‐eye displays (NEDs) create virtual images that may require new photometer designs with small entrance pupils to properly measure the optical performance. A simplified ray trace representation of an NED measured by an appropriately designed photometer is used to explain the need for small entrance pupils and illustrates why conventional large aperture photometer designs can give incorrect results.